Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1021/bi052553y
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen- and Glucose-Dependent Expression of Trhxt1, a Putative Glucose Transporter Gene of Trichoderma reesei,

Abstract: The filamentous fungus Trichoderma reesei is adapted to nutrient-poor environments, in which it uses extracellular cellulases to obtain glucose from the available cellulose biomass. We have isolated and characterized Trhxt1, a putative glucose transporter gene, as judged by the glucose accumulation phenotype of a DeltaTrhxt1 mutant. This gene is repressed at high glucose concentrations and expressed at micromolar levels and in the absence of glucose. The gene is also induced during the growth of T. reesei on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
(70 reference statements)
2
18
0
Order By: Relevance
“…Of the chromosomal clusters with positive correlation to SPPR, three contain typical secondary metabolism genes (c1: non-ribosomal peptide synthase; c9: polyketide synthase; c7: trichothecene C-15 hydroxylase homologue [49] ). Four contain carbon source degradation and uptake related genes (c2: xyn1 [50], ThPg1 [51] homologue and two other CAZymes; c3: trhxt1 [52] and three other putative transporters; c6: glucose-methanol-choline (GMC) oxidoreductase; c7: cbh1 [53] and three putative transporters). Of these c1, c6 and c9 contain putative transcription factors of the Zn2Cys6-family.…”
Section: Resultsmentioning
confidence: 99%
“…Of the chromosomal clusters with positive correlation to SPPR, three contain typical secondary metabolism genes (c1: non-ribosomal peptide synthase; c9: polyketide synthase; c7: trichothecene C-15 hydroxylase homologue [49] ). Four contain carbon source degradation and uptake related genes (c2: xyn1 [50], ThPg1 [51] homologue and two other CAZymes; c3: trhxt1 [52] and three other putative transporters; c6: glucose-methanol-choline (GMC) oxidoreductase; c7: cbh1 [53] and three putative transporters). Of these c1, c6 and c9 contain putative transcription factors of the Zn2Cys6-family.…”
Section: Resultsmentioning
confidence: 99%
“…harzianum. The characterized hexose transporter TrHXT1 [20] and xylose transporter TrXLT1 [9] in T. reesei are also in this cluster, suggesting that TrSTR1 is a putative monosaccharide transporter.…”
Section: Identification Of a Putative Sugar Transporter In T Reesei mentioning
confidence: 91%
“…In this regard, the A. niger analyzing the T. reesei transcriptomic response to wheat straw, many of the HMM xylT top scoring transporters were upregulated on this carbon source versus glucose (Bischof et al, 2013;Ries et al, 2013). We also found that the function of three of the top scoring transporters had been studied previously (Huang et al, 2015;Ramos et al, 2006;Saloheimo et al, 2007;Zhang et al, 2013). One of them, TrStr1 (protID 50894) (Huang et al, 2015) was confirmed to function as xylose transporter, while Stp1 (protID 47710) and TrHxt1 (protID 22912) were associated to cellobiose and glucose utilization respectively (Ramos et al, 2006;Zhang et al, 2013).…”
Section: A Niger and T Reesei In Silico Proteome Miningsupporting
confidence: 69%
“…We also found that the function of three of the top scoring transporters had been studied previously (Huang et al, 2015;Ramos et al, 2006;Saloheimo et al, 2007;Zhang et al, 2013). One of them, TrStr1 (protID 50894) (Huang et al, 2015) was confirmed to function as xylose transporter, while Stp1 (protID 47710) and TrHxt1 (protID 22912) were associated to cellobiose and glucose utilization respectively (Ramos et al, 2006;Zhang et al, 2013).…”
Section: A Niger and T Reesei In Silico Proteome Miningsupporting
confidence: 68%